THE ADDITION OF SOME COAGULANT AND VARIATION OF pH ON DEGRADATION OF TEXTILE WASTEWATER USING GAMMA RADIATION - Agustin Sumartono; Winarti Andayani Lindu; Ermin K. Winarno (Universitas Gadjah Mada, 2006)
The degradation and decolouration of textile waste water by gamma irradiation has been studied. Textile wastewater contain a mixture of dyes that difficult to degrade using conventional method, therefore it is necessary to find another method to degrade those dyes. Samples from effluent of textile industry were taken at certain time and have different in colour and condition. The addition of coagulant and radiation to remove the colour of the samples were demonstrated. Four kind of treatments were carried out in this experiment namely addition of coagulant, radiation, variation of pH and radiation, and combination of radiation with the addition of coagulant. The parameters examined were the change of spectra intensity, percentage of sedimentation after the addition of coagulant, and the percentage of the degradation. Combination of irradiation and the addition of coagulant induced decolouration and degradation of the waste.